2017
DOI: 10.1149/2.0871713jes
|View full text |Cite
|
Sign up to set email alerts
|

Communication—A Mechanistic Study on Electrodeposition of Rhenium from Acidic Solution of Ammonium Perrhenate

Abstract: The electroreduction mechanism of ReO4− in acidic solution is investigated intensively via experiments and thermodynamic analysis. High acidity and low ReO4− concentration are the advantageous conditions to fabricate metallic rhenium, while under other conditions only small amount of rhenium oxides can be obtained. The reduction of ReO4− to metallic Re is a multi-step process involving the successive reduction of intermediates. When there is no enough hydrion or the rhenium concentration exceeds a certain valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 13 publications
(13 reference statements)
0
7
0
Order By: Relevance
“…Furthermore, as discussed in Table II, the presence of fructose lowers the electrolyte acidity. Cao et al 38 reported a systematic study on the effect of electrolyte acidity on Re deposition, where a lower acidity was concluded to facilitate the formation of ReO 2 oxides and prevent further reduction to Re metal. This appears to be consistent with the observations here, where the low current efficiency and incorporation of oxide are more pronounced when fructose are present at high concentration.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, as discussed in Table II, the presence of fructose lowers the electrolyte acidity. Cao et al 38 reported a systematic study on the effect of electrolyte acidity on Re deposition, where a lower acidity was concluded to facilitate the formation of ReO 2 oxides and prevent further reduction to Re metal. This appears to be consistent with the observations here, where the low current efficiency and incorporation of oxide are more pronounced when fructose are present at high concentration.…”
Section: Resultsmentioning
confidence: 99%
“…It has been described that the use of high concentrations of the precursor ion ReO 4 – promotes the formation of rhenium oxide. , Cao et al reported obtaining Re 0 without rhenium oxides using low concentrations of ReO 4 – and high concentrations of H 2 SO 4 . To deposit metallic rhenium from solutions with high concentrations of ReO 4 – it is necessary to add high concentrations of salts, like sodium sulfate, in addition to H 2 SO 4 .…”
Section: Rhenium Bulk Substrates Used In Early Electrochemical Studiesmentioning
confidence: 99%
“…Nowadays, most of the studies regarding rhenium are related to bulk surfaces of solid commercial electrodes , or rhenium surfaces obtained electrochemically on different substrates, such as Pt, Au, Cu, ITO, and Si. , The first result of the application of a rhenium electrode for HER was reported in 1975 by Miles and co-workers , that described higher catalytic activity than Os, Ru, and Ni and lower activity than Pd, Pt, Rh, and Ir in 0.1 M H 2 SO 4 with an HER overpotential (η HER ) value of 544 mV at η 2 , respectively. It was not until 2016 that Garcia–Garcia et al reported an onset potential for H 2 of 350 mV, with an overpotential of 470 mV at η 2 , being the first promising data on the catalytic activity of Re in an acidic medium (0.5 M H 2 SO 4 ).…”
Section: Rhenium Bulk Substrates Used In Early Electrochemical Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Electrodeposition of rhenium was typically carried out from a highly acidic electrolyte 7,8 to avoid the formation of Re oxide, which was found to prevent the deposition of metallic Re. 9,10 While metallic Re has been successfully deposited from such electrolytes, hydrogen evolution reaction dominates the cathodic polarization, not only resulting in low current efficiency but also limiting the potential at which Re deposition occurs. Hydrogen can also be incorporated into the film and changes the morphology and property of films.…”
mentioning
confidence: 99%